Age- and gender-specific improvements on health-related quality of life (HRQoL) and cardiovascular fitness in healthy and sporting inactive older adults using a multidimensional exercise program - Schumacher, Anneke; Rahil, David; Krumpolt, Marlene; Prinz, Alexander; Sannemann, Lucas; Witte, Kerstin (Frontiers in Sports and Active Living, 2025)
IntroductionVarious training regimes in older adults yield differing effects on subjective well-being and physical performance, influenced by age, gender, and individual health status, with noted discrepancies between perceived well-being and actual performance.MethodsThis study investigated age- and gender-specific effects of a 24-week multidimensional training program—including popular sports—on 81 sporting inactive, healthy older adults (60–74 years; f = 53, m = 28). Cardiovascular fitness was assessed via Physical Working Capacity 130 and health-related quality of life via ShortForm 36.ResultsWomen and participants aged 65–69 years showed the greatest subjective health gains and improvements in cardiovascular fitness (p < .001, d = .45). However, Spearman correlations indicated no significant association between subjective Health and objective fitness at baseline (p = .149) or post-intervention (p = .321), nor between changes in performance (total group p = .601; age- and sex-stratified change correlations all p > .191), indicating that women with lower baseline performance did not show systematically larger subjective gains.DiscussionThe program thus offers an effective, non-traditional option to enhance physical fitness and health perception in older adults.